A New Interpretation of Kaldor's First Growth Law for Open Developing Countries - Penélope Pacheco-López; A. P. Thirlwall (University of Kent, School of Economics, 2013)
Kaldors first law of growth posits a positive causal relation between the growth of manufacturing output and the growth of GDP due to static and dynamic returns to scale in manufacturing and rising productivity outside the manufacturing sector as resources are transferred from diminishing returns activities. In an open economy, however, the Kaldor first law of growth is open to another interpretation because it is apparent across countries that there is a close association between manufacturing output growth and export growth, and between export growth and GDP growth. Results are presented for 89 developing countries over the period 1990-2011, also distinguishing between low income, lower-middle income and upper-middle income countries, and between the continents of Africa, Asia and Latin America.
Keywords: C21; E12; F43; 330; Kaldors growth laws; manufacturing growth; export growth; GDP growth